A 0.6 V 2.7 mW 94.3% locking range injection‐locked frequency divider using modified varactor‐less Colpitts oscillator topology. Issue 7 (17th March 2021) - Li, Zhen; Li, Zhenrong; Quan, Xing; Wang, Zeyuan; Li, Xinyu; Zhuang, Yiqi
Abstract: This study presents a 4.6–12.8 GHz injection‐locked frequency divider (ILFD) based on modified varactor‐less Colpitts oscillator topology. A modified Colpitts ILFD is proposed to improve the LR and reduces power consumption, simultaneously. Meanwhile, the forward body bias technique is utilized to further decrease power consumption. Based on the 55 nm CMOS technology, a modified varactor‐less Colpitts ILFD with a free‐running frequency of 4.05 GHz is implemented. The proposed modified varactor‐less Colpitts ILFD exhibits 94.3% LR from 4.6 to 12.8 GHz with an injection power of 0 dBm. It consumes 2.7 mW power from 0.6 V supply voltage and the core area is 0.38 mm 2 .